2011
DOI: 10.1007/s00296-011-1872-4
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum as a method for detection of systemic sclerosis-related interstitial lung disease

Abstract: Inducted sputum (IS) is a non-invasive procedure that can be used for collection of airway secretions. The aim of our study is to evaluate the clinical usefulness of IS for detection of airway inflammation in systemic sclerosis (SSc). Bronchoalveolar lavage and IS were performed to 20 patients with SSc. Eighteen patients who were referred to pulmonary medicine for bronchoalveolar lavage due to other reasons were also recruited for cell counts comparisons. Spirometry, echocardiography and thorax CT (HRCT) imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Yilmaz et al 23 also reported an increase in mean macrophage and lymphocyte counts in the induced sputum of 20 subjects with systemic sclerosis compared with the control group, but unlike in other studies, including ours, they demonstrated a decreased number of neutrophils in the induced sputum of subjects with systemic sclerosis in comparison with the control group. In addition, in our study, we also found correlations between clinical and lung functional parameters and induced sputum findings in the total patient population and in those with restrictive PFT pattern.…”
Section: Discussioncontrasting
confidence: 77%
“…Yilmaz et al 23 also reported an increase in mean macrophage and lymphocyte counts in the induced sputum of 20 subjects with systemic sclerosis compared with the control group, but unlike in other studies, including ours, they demonstrated a decreased number of neutrophils in the induced sputum of subjects with systemic sclerosis in comparison with the control group. In addition, in our study, we also found correlations between clinical and lung functional parameters and induced sputum findings in the total patient population and in those with restrictive PFT pattern.…”
Section: Discussioncontrasting
confidence: 77%
“…Progressive fibrosis in the skin and lungs are prominent, and ultimately leads to organ failure accounting for the substantial mortality of SSc [ 2 ]. Inflammatory infiltrates are observed in a variety of affected organs in early-stage disease [ 3 5 ] and are accompanied by elevated circulating levels of inflammatory cytokines and chemokines [ 6 , 7 ]. Serum amyloid A (SAA) is an evolutionarily conserved ˜ 12 kDa acute phase protein [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damjanov et al [26] studying the IS of 68 SSc-ILD patients (versus 18 HV) observed a significant increase in total number of inflammatory cells, of neutrophils, lymphocytes and eosinophils, and lower macrophages, in SSc patients. Yialmaz et al [27] studying the IS of 17 SSc-ILD patients (versus 12 non-ILD pulmonary controls) observed a significant increase in total number of inflammatory cells, of lymphocytes and macrophages, and lower neutrophils, in SSc patients. Litinsky et al [25] studying the IS of 20 SSc-patients (versus 16 HV) reported an isolated decrease in lymphocytes (p=0.045), with no change in the percentage of neutrophils, macrophages and eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…The cell suspension was then centrifuged again at 400 g at 4 □C for 10 min. Squamous cells, total cell counts and cell viability checked by trypan blue exclusion were performed with a manual hemocytometer [27]. The differential leukocyte count was obtained using a cytospin stained with Rapi Diff II (Atom Scientific, Manchester UK) on 500 non squamous cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation